On the Stability of Deinoxanthin Exposed to Mars Conditions during a Long-Term Space Mission and Implications for Biomarker Detection on Other Planets - Leuko, Stefan; Bohmeier, Maria; Hanke, Franziska; Böettger, Ute; Rabbow, Elke; Parpart, Andre; Rettberg, Petra; de Vera, Jean-Pierre P. (Frontiers in Microbiology, 2017)
Outer space, the final frontier, is a hostile and unforgiving place for any form of life as we know it. The unique environment of space allows for a close simulation of Mars surface conditions that cannot be simulated as accurately on the Earth. For this experiment, we tested the resistance of Deinococcus radiodurans to survive exposure to simulated Mars-like conditions in Low-Earth Orbit (LEO) for a prolonged period of time as part of the BIOMEX (Biology and Mars experiment) project. Special focus was placed on the integrity of the carotenoid deinoxanthin, which may serve as a potential biomarker to search for remnants of life on other planets. Survival was investigated by evaluating colony forming units (CFU), damage inflicted to the 16S rRNA gene by quantitative PCR (qPCR), and the integrity and detectability of deinoxanthin by Raman spectroscopy. Exposure to space conditions had a strong detrimental effect on the survival of the strains and the 16S rRNA integrity, yet results show that deinoxanthin survives exposure to conditions as they prevail on Mars. Solar radiation is not only strongly detrimental to the survival and 16S rRNA integrity but also to the Raman signal of deinoxanthin. Samples not exposed to solar radiation showed only minuscule signs of deterioration. To test whether deinoxanthin is able to withstand the tested parameters without the protection of the cell, it was extracted from cell homogenate and exposed to high / low temperatures, vacuum, germicidal UV-C radiation and simulated solar radiation. Results obtained by RAMAN investigations showed a strong resistance of deinoxanthin against outer space and Mars conditions, with the only exception of the exposure to simulated solar radiation. Therefore, deinoxanthin proved to be a suitable easily detectable biomarker for the search of Earth-like organic pigment-containing life on other planets.